Case Study Of The Battle Of Red Cliff In The Late Han Dynasty Era - Deni Yulyadi; Lukman Y Prakoso; Rudi Sutanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The Battle of Red Cliff, also known as the Battle of Chibi, was a decisive naval battle in the winter of 208-209 AD during the late Han Dynasty, about twelve years before the beginning of the Three Kingdoms Period in Chinese history, the battle was fought between the allied forces of Sun Quan, Liu Bei and Liu Qi against the superior forces of the Northern Warlord Premier Cao Cao. Liu Bei and Sun Quan thwarted Cao Cao's attempt to conquer the southern Yangtze River and reunite the Eastern Han Dynasty Kingdom. In this river warfare, the superiority of weather, wind direction, knowledge of the seasons, and war strategy using ships became dominant compared to the number of troops, knowledge of the terrain was the key to the victory of Liu Bei and Sun Quan's alliance. From this story we can learn that the superior power was defeated by the weaker Imperior Power but had the right Strategy at the right time and the Red Cliff was a witness to the battle of the two warring parties, where the Liu Bei and Sun Quan alliance became the Winner.